Dupilumab. Issue 4 (July 2018) - Sung, Calvin T.; Jacob, Sharon E.
Abstract : ABSTRACT: Drugs are broadly defined as any chemical substance that can elicit a physiological effect on the body. Medication is a subgroup of drugs utilized by healthcare providers to diagnose, treat, or prevent diseases from occurring. Therapeutic monoclonal antibodies are immunotherapies that have gained commercial interest over the past 30 years within the biopharmaceutical sector. In addition to cancer and rheumatology diseases, common dermatological pathologies traditionally limited to topical steroid therapies through immunotherapies can now be targeted with specific immunomodulatory drugs. This pharmacological column aims to draw attention to the first targeted monoclonal antibody therapy approved by the Food and Drug Administration for the treatment of moderate-to-severe atopic dermatitis, dupilumab (Dupixent). The purpose of this article is to review dupilumab within the context of atopic dermatitis immunology, standard treatments, indications, mechanisms of action, adverse reactions, and upcoming applications for asthma with relevance to the growing biopharmaceutical sector. As the popularity of immunotherapies has grown, so has the need for nurse practitioners and educators to continue expanding their knowledge base in drug delivery, adverse reaction management, and therapeutic opportunities to advance care.